Hybrid foldamer with unique architecture from conformationally constrained aliphatic-aromatic amino acid conjugate - Srinivas, Deekonda; Gonnade, Rajesh G.; Ravindranathan, Sapna; Sanjayan, Gangadhar J. (Tetrahedron, 2006)
In this paper, we describe the design and synthesis of a novel hybrid foldamer, derived from a conformationally constrained aliphatic-aromatic amino acid conjugate that adopts a well-defined, compact, three-dimensional structure, governed by a combined conformational restriction imposed by the individual amino acids from which the foldamer is composed. Conformational investigations confirmed the prevalence of a unique doubly bent conformation for the foldamer, in both solid and solution states, as evidenced from single crystal X-ray and 2D NOESY studies, respectively. The findings suggest that constrained aliphatic-aromatic amino acid conjugates offer new avenues for the de novo design of hybrid foldamers with distinctive structural architectures. Furthermore, the de novo design strategy disclosed herein has the potential for significantly augmenting the `tool-box' of the modern day peptidominetic chemist, as well as providing a novel approach to the field of rational design. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Amino acids; Conformation; Foldamer; Peptidomimetics

Enforcing periodic secondary structures in hybrid peptides: a novel hybrid foldamer containing periodic gamma-turn motifs - Baruah, Pranjal K.; Sreedevi, N. K.; Gonnade, Rajesh G.; Ravindranathan, Sapna; Damodaran, Krishnan; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2007)
{This note describes the design, synthesis, and conformational studies of a novel hybrid foldamer that adopts a definite compact, three-dimensional structure determined by a combined effect of the special conformational properties of the foldamer constituents. The striking feature of this de novo designed foldamer is its ability to display periodic gamma-turn conformations stabilized by intramolecular hydrogen bonds. Conformational investigations by single-crystal X-ray studies, solution-state NMR, and ab initio MO theory at the HF/6-31G*
Keywords: ammonia-TPD; benzylation reaction; Ce-Al-MCM-41; Friedel-Crafts alkylation; pyridine-FrIR

Changes in dynamics of SRE-RNA on binding to the VTS1p-SAM domain studied by C-13 NMR relaxation - Oberstrass, Florian C.; Allain, Frederic H. T.; Ravindranathan, Sapna (Journal of the American Chemical Society, 2008)
RNA recognition by proteins is often accompanied by significant changes in RNA dynamics in addition to conformational changes. However, there are very few studies which characterize the changes in molecular motions in RNA on protein binding. We present a quantitative C-13 NMR relaxation study of the changes in RNA dynamics in the pico-nanosecond time scale and micro-millisecond time scale resulting from interaction of the stem-loop SRE-RNA with the VTS1p-SAM domain. C-13 relaxation rates of the protonated carbons of the nucleotide base and anomeric carbons have been analyzed by employing the model-free formalism, for a fully C-13/N-15-labeled sample of the SRE-RNA in the free and protein-bound forms. In the free RNA, the nature of molecular motions are found to be distinctly different in the stem and the loop region. On binding to the protein, the nature of motions becomes more homogeneous throughout the RNA, with many residues showing increased flexibility at the aromatic carbon sites, while the anomeric carbon sites become more rigid. Surprisingly, we also observe indications of a slow collective motion of the RNA in the binding pocket of the protein. The observation of increased motions on binding is interesting in the context of growing evidence that binding does not always lead to motional restrictions and the resulting entropy gain could favor the free energy of association.

Sheet-forming abiotic hetero foldamers - Baruah, Pranjal K.; Sreedevi, Naduthottiyil K.; Majumdar, Baisakhi; Pasricha, Renu; Poddar, Pankaj; Gonnade, Rajesh G.; Ravindranathan, Sapna; Sanjayan, Gangadhar J. (Chemical Communications, 2008)
Abiotic hetero oligomers, adopting a well-defined extended self-assembled sheet-like structure, derived from conformationally constrained aliphatic and aromatic amino acid residues repeating at regular intervals are reported.

Increase in backbone mobility of the VTS1p-SAM domain on binding to SRE-RNA - Ravindranathan, Sapna; Oberstrass, Florian C.; Allain, Frederic H. T. (Journal of Molecular Biology, 2010)
The sterile alpha motif (SAM) domain of VTS1p, a posttranscriptional gene regulator, belongs to a family of SAM domains conserved from yeast to humans. Even though SAM domains were originally classified as protein-protein interaction domains, recently, it was shown that the yeast VTS1p-SAM and the SAM domain of its Drosophila homolog Smaug can specifically recognize RNA hairpins termed Smaug recognition element (SRE). Structural studies of the SRE-RNA complex of VTS1p-SAM revealed that the SAM domain primarily recognizes the shape of the RNA fold induced by the Watson-Crick base-pairing in the RNA pentaloop. Only the central G nucleotide is specifically recognized. The VTS1p-SAM domain recognizes SRE-RNAs with a CNGGN pentaloop where N is any nucleotide. The C1-G4 base pair in the wild type can be replaced by any pair of nucleotides that can form base pairs even though the binding affinity is greatest with a pyrimidine in position 1 and a purine in position 4. The interaction thus combines elements of sequence-specific and non-sequence-specific recognitions. The lack of structural rearrangements in either partner following binding is rather intriguing, suggesting that molecular dynamics may play an important role in imparting relaxed specificity with respect to the exact combination of nucleotides in the loop, except for the central nucleotide. In this work, we extend our previous studies of SRE-RNA interaction with VTS1p, by comparing the dynamics of the VTS1p-SAM domain both in its free form and when bound to SRE-RNA. The 1 5 N relaxation studies of backbone dynamics suggest the presence of a dynamic interaction interface, with residues associated with specific G3 recognition becoming more rigid on RNA binding while other regions attain increased flexibility. The results parallel the observations from our studies of dynamics changes in SRE-RNA upon binding to VTS1p-SAM and shows that molecular dynamics could play a crucial role in modulating binding affinity and possibly contribute to the free energy of the interaction through an entropy-driven mechanism. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: (15)N relaxation; NMR; protein-RNA interaction; SRE-RNA; VTS1p-SAM domain

Structure determination and dynamics of protein-RNA complexes by NMR spectroscopy - Dominguez, Cyril; Schubert, Mario; Duss, Olivier; Ravindranathan, Sapna; Allain, Frederic H. T. (Progress in Nuclear Magnetic Resonance Spectroscopy, 2011)
Keywords: Dynamics; NMR spectroscopy; Protein-RNA complex; Structure determination

Silk fibroin-sophorolipid gelation: deciphering the underlying mechanism - Dubey, Parul; Kumar, Sugam; Aswal, Vinod K.; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R.; Prabhune, Asmita; Nisal, Anuya (Biomacromolecules, 2016)
Silk fibroin (SF) protein, produced by silkworm Bombyx mori, is a promising biomaterial, while sophorolipid (SL) is an amphiphilic functional biosurfactant synthesized by nonpathogenic yeast Candida bombicola. SL is a mixture of two forms, acidic (ASL) and lactonic (LSL), which when added to SF results in accelerated gelation of silk fibroin. LSL is known to have multiple biological functionalities and hence hydrogels of these green molecules have promising applications in the biomedical sector. In this work, SANS, NMR, and rheology are employed to examine the assembling properties of individual and mixed SLs and their interactions with SF to understand the mechanism that leads to rapid gelation. SANS and NMR studies show that ASL assembles to form charged micelles, while LSL forms micellar assemblies and aggregates of a mass fractal nature. ASL and LSL together form larger mixed micelles, all of which interact differently with SF. It is shown that preferential binding of LSL to SF causes rapid unfolding of the SF chain leading to the formation of intermolecular beta sheets, which trigger fast gelation. Based on the observations, a mechanism for gelation of SF in the presence of different sophorolipids is proposed.

Tuning emission responses of a triphenylamine derivative in host-guest complexes and an unusual dynamic inclusion phenomenon - Gangopadhyay, Monalisa; Mandal, Amal K.; Maity, Arunava; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R.; Das, Amitava (Journal of Organic Chemistry, 2016)
A newly synthesized triphenylamine derivative (1Cl(3)) shows significant differences in inclusion complex formation with two different macrocyclic hosts, cucurbit[7]uril (CB[7]) and beta-cyclodextrin (beta-CD). Detailed investigations by NMR spectroscopy reveal that CB[7] forms a 1:3 host-guest complex ([1 center dot 3{CB[7]}]Cl-3) in which three arms of 1Cl(3) are bound to three host molecules. On the other hand, beta-CD forms a dynamic 1:1 inclusion complex ([1 center dotbeta-CD]Cl-3) by binding to only one of the three arms of 1Cl(3) at a given time. The formation of a 1:1 host-guest complex with beta-CD and 1:3 host-guest complex with CB[7] was also confirmed from the results of the isothermal titration calorimetric studies. Interestingly, 1Cl(3) exhibits a rare dual emission property in solution at room temperature with the lower and higher energy bands arising from a locally excited state and an intramolecular charge-transfer transition, respectively. The difference in inclusion complex formation behavior of 1Cl(3) with the two macrocyclic hosts results in the stabilization of different emission states in the two inclusion complexes. The fundamental difference in the electrostatic surface potentials, cavity polarities, and shapes of the two macrocyclic hosts could account for the formation of the different inclusion complexes with distinct luminescence responses.

Chiral discrimination through h-1 nmr and luminescence spectroscopy: dynamic processes and solid strip for chiral recognition - Gangopadhyay, Monalisa; Maity, Arunava; Dey, Ananta; Rajamohanan, P. R.; Ravindranathan, Sapna; Das, Amitava (Chemistry-A European Journal, 2017)
The appropriate choice of the host molecules with well-defined optical activity (S-H/R-H) helps in the differentiation between two secondary ammonium ion-derivative guest molecules with different optical activities (R-G/S-G) based on the fluorescence resonance energy transfer (FRET)based luminescence responses. Crown ether-based host molecules with opposite chiral configurations (R-H, S-H) have been derived from 1,1'-bi-2-naphthol (BINOL) derivatives that have axially chiral biaryl centers. These chiral crown ethers form host-guest complexes (i.e., [2] pseudoro-taxanes) with chiral secondary ammonium ion derivatives (R-G, S-G). NMR spectroscopic studies show that the complexes are in a dynamic equilibrium in solution. Results of the H-1 NMR and fluorescence spectroscopic studies indicate a head-on orientation of the host and guest in the [2] pseudorotaxanes. The difference in the efficiency in the FRET-based responses between anthracene and the BINOL derivatives allow efficient chiral discrimination of the guests. Isothermal titration calorimetry and NMR investigations reveal that inclusion complexes between hosts and guests of the same chirality (R-H center dot R-G, S-H center dot S-G) are more stable relative to those of opposite chirality (R-H center dot S-G, S-H center dot R-G). However, FRET-based energy-transfer efficiency is higher for R-H center dot S-G and S-H center dot R-G complexes. NMR spectroscopic studies show that the relative orientation of the guest in the host cavity is significantly different when the host binds a guest of the same or opposite chirality; furthermore, the latter is more favorable for FRET, thus enabling discrimination between enantiomers. Interestingly, chiral discrimination of guest ions could also be achieved by using silica surfaces modified with chiral host molecules.

Cucurbit[7]uril induced formation of fret-enabled unilamellar lipid vesicles - Kushwaha, Shilpi; Maity, Arunava; Gangopadhyay, Monalisa; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R.; Das, Amitava (Langmuir, 2017)
A unique fluorescence resonance energy transfer (FRET) process is found to be operational in a unilamellar lipid self-assembly in the aqueous phase. A newly synthesized naphthyl based long chain lipid derivative [N-(naphthalene-1-ylmethyl)tetradecane-1-ammonium chloride, 14NA(+)] forms various self-assembled architectures in the aqueous phase. Controlled changes in lipid concentration lead to a transition of the self-assemblies from micelles to vesicles to rods. In the presence of cucurbit[7]uril (CB7), 14NA(+) forms a host-guest [2]pseudorotaxane complex (CB7(sic)14NA(+)) and secondary interactions lead to the formation of a lipid bilayer with hydrophobic pockets situated in between the layers. The change in the structure of 14NA(+) assemblies, interaction with CB7 and formation of supramolecular assemblies of CB7(sic)14NA(+) were examined using light scattering, spectroscopic, and microscopic techniques. Entrapment of a luminescent dye, anthracene within the hydrophobic bilayer of the supramolecular assembly CB7(sic)14NA(+) favors a modified luminescent response due to an efficient FRET process. Further, the FRET process could be controlled by thermal and chemical stimuli that induce transformation of unilamellar vesicles.

pH dependent sophorolipid assemblies and their influence on gelation of silk fibroin protein - Dubey, Parul; Kumar, Sugam; Ravindranathan, Sapna; Vasudevan, Sahana; Aswal, Vinod K.; Rajamohanan, Pattuparambil R.; Nisal, Anuya; Prabhune, Asmita (Materials Chemistry and Physics, 2018)
Sophorolipid (SL), a bio-derived surfactant is an excellent gelling agent for natural fibrous protein, silk fibroin (SF) leading to potential biomedical applications. Interaction of SF with SL has been shown to accelerate the formation of hydrogel with the rate being dependent on the form of SL used. Here, we examine the effect of pH on SL-SF interaction and gel formation by employing rheology, fluorescence spectroscopy, SANS and NMR. The results indicate that the size of SL assemblies decrease as pH increases from acidic to alkaline and significantly impacts the association of SL and SF. The association of SF and SL is mainly via hydrophobic interactions, with the SL molecules forming bead like structures along the SF chain. The increased charge on the acidic form of SL at higher pH results in greater repulsion between acidic SL molecules, which are bound to the hydrophobic sites of SF, leading to rapid chain unfolding and subsequent gelation. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Assemblies; Nuclear magnetic resonance spectroscopy; pH; Silk fibroin; Small angle neutron scattering; Sophorolipid

Thermo thickening behavior of MPEG-b-PCL grafted poly(acrylic acid): a molecular insight - Tiwari, Neha (Polymer, 2018)
We report on the synthesis and characterization of a new thermothickening polymer (PAA-g-(MPEG-b-PCL)) based on the grafting of a block copolymer of mono methoxy poly (ethylene glycol)–b-poly (caprolactone) (MPEG-b-PCL) onto poly (acrylic acid) (PAA). Rheological experiments reveal that aqueous solutions of PAA-g-(MPEG-b-PCL) exhibit interesting irreversible thermothickening behavior above a certain polymer concentration and critical temperature. Light scattering experiments show that increasing temperature induces hydrophobic associations and subsequent aggregation leading to gel formation which is irreversible. The mechanism of thermo thickening was examined at the molecular level by NMR methods which indicated unassembled and assembled environments of the MPEG-b-PCL grafts. On heating, interactions between the graft side chains are significantly enhanced and molecular mobility in the assembled microdomains is reduced. The stable well ordered microdomains that are formed on heating are retained on cooling thus, leading to irreversible gelation.
Keywords: Hydrophobically modified poly (acrylic acid); Light scattering; Methoxy polyethylene glycol-b-polycaprolactone (MPEG-b-PCL) copolymer; Rheology; Thermo gelation

Charge transfer liquid: a stable donor-acceptor interaction in the solvent-free liquid state - Wakchaure, Vivek Chandrakant; Pillai, Lekshmi, V; Goudappagouda; Ranjeesh, Kayaramkodath Chandran; Chakrabarty, Suman; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R; Babu, Sukumaran Santhosh (Chemical Communications, 2019)
Charge-transfer complexes have been an inspiration to develop many functional soft materials. However, most of those studies have focused on solution based assemblies wherein the explicit control of solvents and their polarity are crucial. In this context, we explore an efficient and stable charge transfer liquid using a solvent-free liquid dialkoxynaphthalene donor and a naphthalenediimide acceptor. It has been observed that irrespective of the donor-acceptor ratio, the charge-transfer liquid exhibited an unprecedented stability and retained characteristic features even at increased temperatures. The underlying intermolecular interactions leading to efficient CT have been examined by NMR techniques together with theoretical modelling studies. The concept of charge transfer liquid will be highly beneficial for the development of processable optoelectronically active materials.

Silk fibroin-sodium dodecyl sulfate gelation: molecular, structural, and rheological insights - Hirlekar, Swarali; Ray, Debes; Aswal, Vinod K.; Prabhune, Asmita; Nisal, Anuya; Ravindranathan, Sapna (Langmuir, 2019)
A gelling agent is necessary to accelerate sol to gel transition in an aqueous solution of silk fibroin (SF), which otherwise takes several days to complete. In this paper, we investigate the mechanism of gelation of Bornbyx mori SF by a model anionic surfactant, sodium dodecyl sulfate (SOS). Even though interactions between SDS and proteins have been extensively investigated, most of these studies have focused on globular proteins, which undergo denaturation. The interaction with a fibrous protein such as SF is different and results in an altered secondary structure leading to gelation. In this work, the concentration-dependent gelation process of the SF-SDS system is examined using rheology, SANS, FTIR, and NMR. We observed preferential binding of SDS to specific regions on the SF chain, which aids structural changes favoring beta-sheet formation. We propose a mechanism for the accelerated sol-gel transition in the SF-SDS system.

Polymer nanorings with uranium specific clefts for selective recovery of uranium from acidic effluents via reductive adsorption - Kushwaha, Shilpi; Mane, Manoj; Ravindranathan, Sapna; Das, Amitava (ACS Sensors, 2020)
Nanostructured polymeric materials, functionalized with an appropriate receptor, have opened up newer possibilities for designing a reagent that shows analyte-specific recognition and efficient scavenging of an analyte that has either a detrimental influence on human physiology and environment or on its recovery for further value addition. Higher active surface area, morphological diversity, synthetic tunability for desired surface functionalization, and the ease of regeneration of a nanostructured material for further use have provided such materials with a distinct edge over conventional reagents. The use of a biodegradable polymeric backbone has an added significance owing to the recent concern over the impact of polymers on the environment. Functionalization of biodegradable sodium alginate with AENA (6.85% grafting) as the receptor functionality led to a unique open framework nanoring (NNRG) morphology with a favorable spatial orientation for specific recognition and efficient binding to uranyl ions (U) in an aqueous medium over a varied pH range. Nanoring morphology was confirmed by transmission electron microscopy and atomic force microscopy images. The nanoscale design maximizes the surface area for the molecular scavenger. A combination of all these features along with the reversible binding phenomenon has made NNRG a superior reagent for specific, efficient uptake of UO22+ species from an acidic (pH 3-4) solution and compares better than all existing UO22+-scavengers reported till date. This could be utilized for the recovery of uranyl species from a synthetic acidic effluent of the nuclear power. The results of the U uptake experiments reveal a maximum adsorption capacity of 268 mg of U per g of NNRG in a synthetic nuclear effluent. X-ray photoelectron spectroscopy studies revealed a reductive complexation process and stabilization of U(IV)-species in adsorbed uranium species (U@NNRG).
Keywords: biodegradable polymeric backbone; molecular recognition; nanostructured material; sodium alginate; uranium; uranyl-specific receptor

Self-assembly of bispentadecylphenol substituted perylenediimide with PS-b-P4VP for structure-property insight into the core of core-shell micelles - Roy, Moumita; Rajamohanan, Pattuparambil R.; Ravindranathan, Sapna; Asha, S. K. (ACS Applied Polymer Materials, 2020)
We report the use of a ditopic molecular probe bispentadecylphenol substituted perylenediimide (PBI-PDP) to examine the molecular level self-assembly of polystyrene-b-poly(4-vinylpyridine) (PS-b-P4VP) in tetrahydrofuran (THF). A series of complexes were prepared between PS-b-P4VP copolymers with varying lengths of the 4-vinylpyridine chain and PBI-PDP. Light scattering and NMR spectroscopic studies reveal that the self-assembled structures of the solid complexes are not fully disrupted when the complexes are dissolved in THF. NMR experimental parameters measured for the small probe molecule provide detailed insights into the structure of the assemblies in solution as well as the interaction between the small molecule and the block copolymer. Such insights can have important implications in manipulating the nanostructure of block copolymer micelles to suit various application requirements. The dynamics and distribution of the PBI-PDP molecules within the assemblies in solution show a dependence on the length of the P4VP block. Transmission electron microscopy was employed to study the evolution of morphologies in films prepared from the self-assembled structures in THF solutions.
Keywords: core corona interface; ditopic molecular probe; environment; micelles; perylenediimide; PS-b-P4VP; Self-assembly

Transient alpha-helix in the N-terminal RNA recognition motif of polypyrimidine tract binding protein senses RNA secondary structure - Maris, Christophe; Jayne, Sandrine; Damberger, Fred F.; Beusch, Irene; Dorn, Georg; Ravindranathan, Sapna; Allain, Frederic H-T (Nucleic Acids Research, 2020)
The polypyrimidine tract binding protein (PTB) is a multi-domain protein involved in alternative splicing, mRNA localization, stabilization, polyadenylation and translation initiation from internal ribosome entry sites (IRES). In this latter process, PTB promotes viral translation by interacting extensively with complex structured regions in the 5'-untranslated regions of viral RNAs at pyrimidine-rich targets located in single strand and hairpin regions. To better understand how PTB recognizes structured elements in RNA targets, we solved the solution structure of the N-terminal RNA recognition motif (RRM) in complex with an RNA hairpin embedding the loop sequence UCUUU, which is frequently found in IRESs of the picornovirus family. Surprisingly, a new three-turn alpha 3 helix C-terminal to the RRM, folds upon binding the RNA hairpin. Although alpha 3 does not mediate any contacts to the RNA, it acts as a sensor of RNA secondary structure, suggesting a role for RRM1 in detecting pyrimidine tracts in the context of structured RNA. Moreover, the degree of helix formation depends on the RNA loop sequence. Finally, we show that the alpha 3 helix region, which is highly conserved in vertebrates, is crucial for PTB function in enhancing Encephalomyocarditis virus IRES activity.

Excimer to exciplex transition through realization of donor-acceptor interactions in luminescent solvent-free liquids - Wakchaure, Vivek Chandrakant; Goudappagouda; Das, Tamal; Ravindranathan, Sapna; Babu, Sukumaran Santhosh (Nanoscale, 2021)
Luminescent solvent-free organic liquids are known for their enhanced quantum yield, color tunability, and availability of a matrix for other dopants to generate hybrid luminescent materials with improved features for newer applications. Herein, we report a donor-acceptor based luminescent ``exciplex liquid'' by utilizing the slightly different electron affinity of the acceptor molecules. A red-shifted broad exciplex emission exhibited by the donor-acceptor pair even at a lower concentration of the acceptor (0.001 equiv.) indicates high efficiency in the solvent-free state. A detailed NMR study revealed weak intermolecular interactions between the donor and acceptor in the solvent-free matrix that stabilizes the exciplex liquid. The failure of structurally similar solid counterparts to form an exciplex confirms the advantage of the available supportive liquid matrix. Besides, the luminescent exciplex liquid is found efficient in sensing application, which is unachievable by either the individual liquids or their solid counterparts. Here, a transition of a donor-acceptor pair from a solid to solvent-free liquid results in a new hybrid liquid that can be an alternative for solid sensor materials.

Donor-acceptor based solvent-free organic liquid hybrids with exciplex emission and room temperature phosphorescence - Wakchaure, Vivek Chandrakant; Veer, Sairam D.; Nidhankar, Aakash D.; Goudappagouda; Nayak, Rashmi; Asokan, Kiran; Ravindranathan, Sapna; Babu, Sukumaran Santhosh (Chemical Communications, 2022)
Solvent-free organic liquids are well-known for their excellent luminescence features. Hence, the recent developments in this area have marked them as potential emitters with high quantum yield and enhanced processability. The support of an available liquid matrix enables doping to deliver hybrid liquids with intriguing luminescence features. In this direction, we report solvent-free liquid donor-acceptor pairs with exciplex emission and room temperature phosphorescence at very low acceptor loading. The underlying weak intermolecular interactions have been revealed by 2D NMR techniques and theoretical calculations. The formation of large-area thin films by exciplex and phosphorescent liquid hybrids will encourage the development of scalable lighting and display materials.

Investigation of domain structures in monomethoxy poly(ethylene glycol)-b-poly(caprolactone) grafted poly(acrylic acid) by NMR diffusion studies - Tiwari, Neha; Badiger, Manohar Virupax; Rajamohanan, Pattuparambil Ramanpillai; Ravindranathan, Sapna (Polymer International, 2022)
Associating polymers developed by grafting a block copolymer of monomethoxy poly(ethylene glycol)-b-poly(caprolactone) (MPEG-b-PCL) onto poly(acrylic acid) undergo an irreversible sol-gel transition on heating. The influence of various physicochemical parameters on the thermoresponsive behaviour was examined by rheology and NMR studies. Pulsed field gradient NMR diffusion studies were performed to probe the mechanism of thermally induced gelation. Analysis of the diffusion data reveals the presence of loosely and strongly associated structures which respond differently to variation in temperature. It is observed that the polymer solution, which is visibly homogeneous, is heterogeneous on a mesoscopic scale with a distribution of domains. Detailed investigation of the thermally induced sol-gel transition shows that the mechanism of gelation involves irreversible alterations in the domain structure and size. (c) 2022 Society of Industrial Chemistry.
Keywords: associating polymers; hydrophobically modified polymers; NMR diffusion studies; Rheology; sol-gel transition; thermoresponsive polymers

On the competition between six-membered and five-membered NHC towards alane centered ring expansion - Balayan, Kajal; Sharma, Himanshu; Vanka, Kumar; Ravindranathan, Sapna; Gonnade, Rajesh G.; Sen, Sakya S. (Chemical Communications, 2023)
The combination of 6-SIDipp center dot AlH3 (1) and 5-IDipp resulted in the ring expansion of 6-NHC, while the five-membered NHC remained unchanged, which was subsequently explained by DFT studies. Besides, the substitution chemistry of 1 was also studied with TMSOTf and I-2, which gave rise to the substitution of a hydride by triflate or iodide ligands.

Donor strapped perylene bisimide macrocycle and its lemniscate dimer with extended charge separation - Veer, Sairam Dnyaneshwar; Goswami, Tanmay; Ravindranathan, Sapna; Gonnade, Rajesh; Kharbanda, Nitika; Ghosh, Hirendra N.; Babu, Sukumaran Santhosh (Inorganic Chemistry Frontiers, 2023)
Macrocyclic structures are fascinating due to their unique design and capability to place chromophores in specific orientations, resulting in exciting optoelectronic properties. However, the synthetic challenges limit the broad exploration of such systems. Herein, we report a thiophene-diacetylene-based ring strapped perylene bisimide macrocycle and its notably different electron transfer features. Single-crystal analysis of the macrocycle pointed to the nearly orthogonal placement of donor-acceptor units, facilitating better electronic communication between them. Interestingly, introduction of an alkyl substituent on the peripheral thiophene ring opened the possibility of forming a higher oligomer macrocycle consisting of two strapped perylene bisimide units. Diffusion and two-dimensional NMR experiments provided insight into the structure of the figure-eight-shaped lemniscate dimer. Transient absorption measurements showed faster electron transfer and extended stabilization of the charge-separated state. The thiophene-diacetylene-based ring is a better donor unit to facilitate rapid electron transfer and extended charge separation in the macrocycle and its lemniscate dimer. The new macrocycle design enables the formation of higher analogs equally capable of stabilizing the charge-separated state. Donor-acceptor (D-A) macrocycle designs position the respective units to achieve ultrafast electron transfer precisely and an extended charge-separated state. Here, we report a D-A macrocycle and its lemniscate dimer molecule with exciting electron transfer features.

Unlike RNA-TBA (rTBA), iso-rTBA, the 2 `-5 `-linked RNA-thrombin-binding aptamer, is a functional equivalent of TBA - Wagh, Atish A. A.; Kumar, Vaijayanti A. A.; Ravindranathan, Sapna; Fernandes, Moneesha (Chemical Communications, 2023)
An antiparallel, functional RNA G-quadruplex of the 2 `-5 `-linked thrombin-binding aptamer (iso-rTBA) is reported for the first time. It can inhibit clotting and is remarkably stable to nuclease-degradation, besides having high thermal stability. It is thus, a superior candidate to TBA, rTBA or isoTBA, for further development as an anticoagulant.

Insights into the structure of sucralfate by advanced solid- and liquid-state NMR - Hareendran, Chaithanya; Ravindranathan, Sapna; Ajithkumar, T. G. (Molecualr Pharmaceutics, 2024)
Sucralfate, which is a sucrose octasulfate aluminum complex, is an active pharmaceutical ingredient (API) falling in the category of cytoprotective agents which are very effective for gastric and duodenal ulcers. On interaction with stomach acid, it ionizes into aluminum and sucrose octasulfate ions to form a protective layer over the ulcerated region inhibiting further attack from acid. The mechanism of action of sucralfate in the context of its structure is not well understood. Considering that at least two forms of this API are available in the market, there are no reports on the various forms of sucralfate and differences in their pharmacological action. We characterized the two forms of sucralfate using multinuclear, multidimensional solid-state NMR, and the results show significant structural differences between them arising from variation in the aluminum environment and the level of hydration. The impact of structural differences on pharmacological action was examined by studying acid-induced Al release by Al-27 liquid-state NMR. The sucralfate, European pharmaceutical standard, Form I, undergoes faster disruption in acid compared to Form II. The difference is explained on the basis of structural differences in the two forms which gives significant insights into the action of sucralfate in relation to its structure.
Keywords: (27)AlMQMAS; H-1-H-1 DQSQ; pharmacological action; solid-stateNMR; sucralfate

N-terminal domain of polypyrimidine-tract binding protein is a dynamic folding platform for adaptive RNA recognition - Damberger, Fred F.; Krepl, Miroslav; Arora, Rajika; Beusch, Irene; Maris, Christophe; Dorn, Georg; Sponer, Jiri; Ravindranathan, Sapna; Allain, Frederic H-T (NUCLEIC ACIDS RESEARCH, 2024)
Keywords: CHEMICAL-SHIFT ANISOTROPY; NMR; ROTATING-FRAME RELAXATION; TIME-SCALE DYNAMICS

Mechanochemical large-scale rapid synthesis of ultrapure sodium hexafluorophosphate - Senthilkumaran, Marimuthu; Javaregowda, Bharathkumar H.; Rajendran, Prakash Babu; Balasubramanian, Rajalakshmi; Ajithkumar, Thalasseril G.; Ravindranathan, Sapna; Krishnamoorthy, Kothandam (ChemPlusChem, 2025)
Among the sodium battery electrolytes, sodium hexafluorophosphate (NaPF6) exhibits superior conductivity, anodic stability, and stable cathode electrolyte interface compared to other electrolytes. Therefore, the synthesis of pure NaPF6 through a simple process is very important. Usually, NaPF6 is synthesized using HF. In our approach, NaPF6 is synthesized by grinding dry ammonium hexafluorophosphate (NH4PF6) and sodium metal. Sodium injects an electron into the ammonium ion, which results in the formation of ammonia and hydrogen. The gram scale synthesis is completed in about 30 min. Purification of the product is not needed. The product purity is confirmed by various spectroscopic and electrochemical techniques. Usually, NaPF6 comprises NaF, HF, and solvents as impurities that affect the performance of SIBs. It has been confirmed that the NaPF6 synthesized by our mechanochemical approach in the absence of solvent is devoid of impurities despite the absence of product purification step. Furthermore, the synthesis of pure NaPF6 (250 g) is demonstrated using a grinder used as household item in cooking Indian pancakes, which costs about 300 USD. The duration of the synthesis of 250 g pure NaPF6 is 1 h. The purity of this sample is comparable to that of NaPF6 (5 g) synthesized using mortar and pestle.
Keywords: ammonium hexafluorophosphate; Batteries; carbonates; sodium hexafluorophosphate; sodium vanadium phosphate

Probing solvent fluctuations in deep eutectic solvents: Influence of probe charge and nano-domain localization - Chowdhury, Tubai; Pathania, Akhil; Ravindranathan, Sapna; Bagchi, Sayan (Journal of Chemical Physics, 2025)
Deep eutectic solvents (DESs) segregate into hydrogen bond acceptor or hydrogen bond donor (HBD) rich nano-domains, leading to molecular heterogeneity. Understanding how this heterogeneity affects the DES structure and dynamics is essential. In this study, we used two-dimensional nuclear magnetic resonance (2D NMR) and two dimensional infrared (2D IR) spectroscopies, combined with molecular dynamics (MD) simulations, to investigate solvation structure and dynamics in two choline chloride-based DESs with different HBDs-levulinic acid and glycolic acid. We introduced two thiocyanate vibrational probes, methyl thiocyanate (CH3SCN, neutral) and ammonium thiocyanate (NH4SCN, anionic), which selectively localize in specific nano-domains. 2D NMR provided insights into solvent structure and probe location, while 2D IR captured solvation dynamics. Our results show that these small probes do not alter the solvent structure, regardless of charge. However, solvation dynamics depend on long-range electrostatic ordering in the DES and the local shielding effects of the nano-domain where the probe resides. MD simulations complement experimental findings, providing a molecular-level understanding of solvation in DESs.

Insight Into the Influence of Salinity on Flow and Flocculation Behavior of Acrylamide-Based Cationic Polyelectrolyte - Ranganath, Suresha P.; Kurian, Rachna; Torris, Arun; Khairnar, Ajay; Ravindranathan, Sapna; Rajamohanan, P. R.; Badiger, Manohar V.; Wolf, Bernhard A. (Journal of Applied Polymer Science, 2026)
The viscometric behavior of aqueous solutions of acrylamide and acrylamidopropyl trimethylammonium chloride copolymers (AM-co-APTMAC) with varying cationic content under different salinity conditions was studied. Viscometric measurements were employed to determine intrinsic viscosity and quantify the influence of electrostatic interactions on chain conformation. Rheology experiments were performed to probe dynamic flow behavior under shear to obtain insights into polyelectrolyte viscoelastic properties under conditions mimicking industrial processes. Viscometric and rheology data analysis is augmented with insights from NMR relaxation and pulsed field gradient NMR diffusion experiments. Further, flocculation of kaolin suspensions was studied using aqueous solutions of AM-co-APTMAC copolymers with different charge fractions in the presence and absence of salt. The physicochemical insights on the behavior of AM-co-APTMAC polyelectrolytes in solution from this study could be relevant in practical applications, such as plants that use seawater or in cases where the ionic strength of suspensions is high due to salinity in the medium.
Keywords: copolymers; polyelectrolytes; structure property relationships; theory and modeling

Potential tuneable glucose oxidation to selective C6 molecules and CC cleavage, and parallel green H2 production: sustainable high current density electrolysis - Chauhan, Inderjeet; Patra, Kshirodra Kumar; Vijay, Pothoppurathu M.; Nalajala, Naresh; Mehta, Shweta; Joshi, Kavita; Ravindranathan, Sapna; Gopinath, Chinnakonda S. (Chemical Engineering Journal, 2026)
Current study elucidates the electrocatalytic efficacy of palladium-nanocubes (Pd-NCs) for the selective oxidation of glucose to value-added chemicals with concomitant hydrogen evolution. The Pd-NC catalyst demonstrated exceptional activity and product selectivity, achieving nearly quantitative glucose conversion (>99 %) with high gluconic and glucaric acid yield at low anodic overpotential (0.6 V vs. RHE) in alkaline electrolyte. At not-so-high elevated potentials (1.2 V vs. RHE), oxidative CC scission prevails, yielding shorter-chain carboxylates along with C6-acids. Reaction products are thoroughly characterized and quantitatively estimated by NMR spectral methods; NMR methods also provide CC cleavage and mechanistic pathways of glucose to various products. Complementary DFT calculations delineate the thermodynamic favorability of glucose adsorption on Pd-NC surfaces (-1.83 eV) and the exergonic oxidation pathway under applied bias, corroborating experimental product distributions. In a two-electrode electrolyzer, Pd-NC anode paired with Pt/C and Ni2P cathode demonstrates 100 mA/cm(2) at 0.99 V and 1.37 V, respectively, with 48 % reduction in energy input (26.6 kWh/kg H-2) compared to conventional alkaline electrolysis; critically, H-2 production energy is lower than the usable energy (33.3 kWh/kg H-2). Sustainable chronopotentiometric assays confirm sustainability (similar to 140 h) in alkaline as well as saline electrolytes, underscoring the system's resilience against chloride-mediated corrosion. Present work establishes a proof of concept for integrated biomass-component valorization and carbon-negative green hydrogen production, merging atomic-level mechanistic insights with scalable reactor design. Optimization of reaction parameters, including potential tuning, reaction temperature and electrolyte engineering, offers a compelling strategy to further enhance C6 and fragmented product selectivity and overall system efficiency.
Keywords: biomass valorization; electrocatalysis; energy conversion; Sustainability